Critical Thinking Profile and Environmental Literacy Analysis of Al-Washliyah Labuhanbatu University Biology Education Undergraduate Students - Rahmi Syafriyeti; Fitri Endang Srimulat; Witma Novita Atnur (Universitas Labuhanbatu, 2024)
Critical thinking plays a crucial role in enhancing environmental literacy by fostering the ability to analyze, evaluate, and understand complex environmental issues. The purpose of this study was to analyzed the profile of critical thinking and environmental literacy of biology education students at Al-Washliyah Labuhanbatu University. This research is descriptive quantitative in which data were collected through observation and questionnaires. critical thinking indicators are simple explanations, building basic skills, inferring, making further explanations and strategies and environmental literacy indicators knowledge, cognitive skills, attitudes and behaviors related to environmental stewardship. The results showed that the mean score of CT skills (M=13.81, SD=3.52) was weak and below the optimal average (M=17.1, SD=5.0) and the environmental literacy profile shows that for the knowledge indicators the average is 61.25% with a sufficient category, for the cognitive skills indicators 63.95% with a sufficient category, for the attitude indicators 76.53% with a good category, for the environmentally responsible behavior indicators 53.92% with a poor category. Critical thinking skills of biology students at Al-Washliyah Labuhanbatu University is not favorable and environmental literacy for the ecological knowledge aspect is still at a moderate level, which means that some ecological concepts such as biogeochemical cycles are not well understood